Hotel Vendome, Commonwealth Avenue and Dartmouth Street, 1869 - Unknown (Tufts Archival Research Center, 2005)
Street-level view looking southwest across Dartmouth Street toward the Hotel Vendome. Two horse-drawn vehicles are waiting outside the hotel on the street. In the distance in the New Old South Church. This image is part of the Chandler Hovey Collection. 5 3/4 x 8 Photographs